2014
DOI: 10.1016/j.physbeh.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Is fat taste ready for primetime?

Abstract: Mounting evidence suggests that gustation is important for the orosensory detection of dietary fats, and might contribute to preferences that humans, rodents, and possibly other mammals exhibit for fat-rich foods. In contrast to sweet, sour, salty, bitter, and umami, fat is not widely recognized as a primary taste quality. Recent investigations, however, provide a wealth of information that is helping to elucidate the specific molecular, cellular, and neural mechanisms required for fat detection in mammals. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 130 publications
1
47
0
1
Order By: Relevance
“…OA, C 18 H 34 O 2 , is a monounsaturated fatty acid having 18 carbon atoms and one double bond and found in olive oil and many other vegetable and animal oils and fats. In fact, possible lipid receptors have been identified, such as free fatty acid receptor 1 (FFAR1, also known as G-protein coupled receptor 40) and G-protein coupled receptor 120 (GPR120), in some taste receptor cells (type I or type II cells) of the tongue's taste buds (Cartoni et al 2010;DiPatrizio 2014). FFAR1, which is also expressed in many endocrine cells, is activated by medium-chain (6-12 carbons) and long-chain (13-21 carbons) fatty acids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OA, C 18 H 34 O 2 , is a monounsaturated fatty acid having 18 carbon atoms and one double bond and found in olive oil and many other vegetable and animal oils and fats. In fact, possible lipid receptors have been identified, such as free fatty acid receptor 1 (FFAR1, also known as G-protein coupled receptor 40) and G-protein coupled receptor 120 (GPR120), in some taste receptor cells (type I or type II cells) of the tongue's taste buds (Cartoni et al 2010;DiPatrizio 2014). FFAR1, which is also expressed in many endocrine cells, is activated by medium-chain (6-12 carbons) and long-chain (13-21 carbons) fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…GPR120 is also a lipid receptor expressed in the taste buds, as well as in adipocytes and other cells (Gotoh et al 2007;Oh et al 2010;Janssen and Depoortere 2013). Recent studies have shown that GPR120 dysfunction leads to obesity, glucose intolerance, and fatty liver (Ichimura et al 2012;Janssen and Depoortere 2013;DiPatrizio 2014). Moreover, several studies reported a difference in the OA detection threshold among human individuals and an inverse correlation between body mass index (BMI), a measure of body fat, and oral OA sensitivity (Stewart et al 2010(Stewart et al , 2011Haryono et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of CB 1 increases food intake, enhances reward aspects of eating, and promotes energy conservation (4). There is also convincing evidence that the sensory experience associated with the eating of fatty foods is initiated by gustatory signals that require selective receptors on taste bud cells to be engaged by FFAs (62,63). Deletion of genes encoding four distinct candidate receptors has yielded results that support this conclusion.…”
Section: Fat Tastementioning
confidence: 96%
“…The orosensory qualities of fat are a major contributor to the hedonic properties of this macronutrient (63). For example, rats avidly consume corn oil emulsions even under sham feeding conditions, when postingestive feedbacks are absent (see below) (77).…”
Section: Gut Endocannabinoids As Hunger Signalsmentioning
confidence: 99%
“…Sin embargo, todavía existen lagunas en este conocimiento. La evidencia sugiere que tanto el gusto, la textura y el olfato participan en diversos grados en la detección de alimentos grasos a partir de ácidos grasos libres en la cavidad oral y aún existen elementos claves que deben ser abordados para considerar la grasa como un gusto básico (18).…”
Section: El Sentido Del Gustounclassified